METHOD AND SYSTEM FOR OFFLINE CODE VALIDATION - BALASUBRAMANIAM RAJA; ADAVI VISWESWARA PRASAD (2012)
A method of offline code validation and a process control system are provided. The system includes a plurality of sensors each configured to generate a sensor output value representative of a respective sensed parameter in a process plant, at least one process controller configured to receive one or more of the sensor output values and to generate a controller output value using the one or more of the sensor output values and a control algorithm associated with the at least one process controller, a plurality of controlled components configured to receive an associated controller output value, and an offline computing environment including a selectable model controller configurable to represent the at least one process controller, the model controller selectable by a user from code representing the at least one process controller and displayed on a user interface.